Design, Synthesis of New Imidazolium-1,2,3-triazole Hybrid Derivatives as Antimicrobial Agents - Ameer Salem Muttaleb; Nardeen Adnan Berto; Sahar Adeeb Mamoori; Zaman Abdalhussein Ibadi Alaridhee; Ehab Kareem Obaid; Ali Jabbar Radhi (Universitas Gadjah Mada, 2024)
New imidazolium salts with 1,2,3-triazole rings (rm1-rm5) were prepared in the current work using a design-driven synthetic procedure scheme. By using analytical techniques such as NMR, IR and spectral information, the chemical structures of target synthesized products were identified using results that were discovered in perfect accord with their assigned structures. The microorganism used in the current study were bacterial strains of Staphylococcus aureus, Escherichia coli, Klebsiella pneumoniae, Bacillus subtilis and Micrococcus luteus, as well as the fungal strains of Aspergillus niger and Candida albicans. All the end products were estimated for their antibacterial activity. The values for the minimum inhibitory concentration (MIC) were confirmed by comparison to the widely used antibiotics fluconazole and ciprofloxacin as control drugs. Particularly, the compounds (rm5) and (rm4) showed observable antibacterial activity. These compounds might offer a brand-new place to start when looking for new antibacterial medications.